Chinese herbal medicines for the treatment of non-structural abnormal uterine bleeding in perimenopause: A systematic review and a meta-analysis. (December 2018) - Shang, Yujie; Lu, Su; Chen, Yun; Sun, Xiumei
Highlights: The effectiveness and safety of CHM for the treatment of non-structural AUB in perimenopause was analyzed. It appears that CHM can improve the climacteric symptom of non-structural AUB patients. The recurrence rate of patients treated with CHM is lower than those with western therapies. We applied multiple strategies to make the research more rigorous, such as strict criteria, subgroup and sensitivity analysis. Abstract: Objective: Chinese herbal medicines (CHM) have been the mainstream therapy in Asia for thousands of years and become more popular as the alternative treatment recently. The objective of this study is to evaluate the efficacy and safety of CHM for non-structural abnormal uterine bleeding (AUB) in perimenopause. Methods: Seven databases were searched from inception to December 31 st, 2017. Randomized controlled trials (RCTs) which compared CHM versus western therapy in treating non-structural AUB in perimenopause were extracted. The primary outcome measures were hemostasis rate, normalization rate of menstruation, hemoglobin count, and improvement of menopausal symptoms. The secondary outcome measures were adverse effects and recurrence rate. The methodological quality of included trials was assessed in line with the criteria of the Cochrane Risk of Bias assessment tool. Data analyses were performed by Review Manager 5.3 software. The results were expressed as risk ratio (RR) or mean difference (MD) with a 95% confidence interval (CI). Results: Fifteen RCTs with 1344 participants were analyzed. Compared with Western therapies, CHM showed advantages in normalization rate of menstruation (RR 1.20; 95% CI 1.06–1.34; P  = 0.003), improving menopausal symptoms (RR 1.20, 95% CI 1.10–1.31, P <0.0001; MD -2.80, 95% CI -3.35 to -2.25, P <0.00001) and the hemoglobin count (MD 7.85, 95% CI 4.05–11.65, P <0.0001) with lower incidence of adverse reactions (RR 0.23, 95% CI 0.12 to 0.43, P <0.00001) and lower recurrence rate (RR 0.38, 95% CI 0.26 to 0.54, P <0.00001). However, we found insufficient evidence that CHM was any more or less effective than CWT for hemostasis rate (RR 1.02, 95% CI 0.95–1.10, P  = 0.62). Conclusions: The findings of our study suggest that CHM may be the effective, acceptable and safe treatment for non-structural abnormal uterine bleeding during perimenopause when compared with Western medicine. However, due to high clinical heterogeneity, low methodological quality and without a proper placebo control, the conclusion is inconclusive and limited, and it should be further examined and updated in future work.